Covid-19 Pandemic Disaster Mitigation Training as an Effort to Minimize the Spread of Coronavirus in Majalaya Sub-District, Bandung Regency, Indonesia - Sukono Sukono; Endang Soeryana Hasbullah; Yuyun Hidayat (Research Collaboration Community (RCC), 2021)
The Covid-19 pandemic has hit almost all countries in the world, including Indonesia. In addition, the COVID-19 pandemic has also affected the education system in Indonesia, which causes the learning system to be conducted online. However, in some regions in Indonesia, it is allowed to organize a face-to-face learning system. Where according to the direction of the Minister of Education and Culture in the 2021/2022 school year, it will be held with limited face-to-face learning while still implementing health protocols. Through the Community Service program with the topic